Affect, emotion, and subjectivity in early modern Muslim Empires : new studies in Ottoman, Safavid, and Mughal art and culture - Rizvi, Kishwar (Leiden ; Boston : Brill, 2018)
Affect, Emotion and Subjectivity in Early Modern Muslim Empires presents new approaches to Ottoman Safavid and Mughal art and culture. Taking artistic agency as a starting point, the authors consider the rise in status of architects, the self-fashioning of artists, the development of public spaces, as well as new literary genres that focus on the individual subject and his or her place in the world. They consider the issue of affect as performative and responsive to certain emotions and actions, thus allowing insights into the motivations behind the making and, in some cases, the destruction of works of art. The interconnected histories of Iran, Turkey and India thus highlight the urban and intellectual changes that defined the early modern period.
Introduction : affect, emotion, and subjectivity in the early modern period / Kishwar Rizvi -- Chasing after the Muhandis : visual articulations of the architect and architectural historiography / Sussan Babaie -- Who's hiding here? Artists and their signatures in Timurid and Safavid manuscripts / Marianna Shreve Simpson -- Ottoman author portraits in the early-modern period / Emine Fetvaci -- In defense and devotion : affective practices in early modern Turco-Persian manuscript paintings / Christiane Gruber -- Sentiment in silks : Safavid figural textiles in Mughal courtly culture / Sylvia Houghteling -- The city built, the city rendered : locating urban subjectivity in eighteenth-century Mughal Delhi / Chanchal Dadlani / Faiz Dihlavi's female-centered poems and the representation of public life in late Mughal society / Sunil Sharma -- Mevlevi Sufis and the representation of emotion in the arts of the Ottoman world / Jamal J. Elias.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Emotions in art; Art, Ottoman; Art, Mughal Empire; Art, Safavid; Architecture, Mughal Empire; Turkey -- Civilization -- 1288-1918.; India -- Civilization; Iran -- Civilization; Art ottoman; Art moghol; Art séfévide.; Architecture moghole; Empire ottoman -- Civilisation; Inde -- Civilisation; Iran -- Civilisation; ART -- History -- General; Architecture, Mogul Empire; Art, Mogul Empire; Art, Ottoman; Art, Safavid; Civilization; Emotions in art; India; Iran; Turkey; 1288-1918